Islamic Boarding School Tradition a Research Model for Islamic Education by Zamachsyari Dhofier - Syarif Hidayat; Mufti Ali; Nana Surya Permana (International Journal of Nusantara Islam, 2021)
This study will discuss Zamachsyari Dhofier's work on the pesantren tradition. Discussion about the pesantrens, madrasas and schools, written by Zamachsyari Dhofier be very interesting, because it is told how the upheaval of Islam. In the course of history, the origins of schools can not be separated from the arrival and spread of Islam in Indonesia. Because discussion pesantrens have a great impact on the education model in Indonesia.And changes in the form and content of Islamic education in Indonesia can not be separated from the demands of the times that it faces. But the process of change is not an event that is smooth and seamless with no disagreement among those involved in it. Political background of the Dutch colonial education in determining the changes in the world of sports pesantrens, madrasas and schools in Indonesia